Faunal remains from Tel Abel Beth Maacah: Social change in the late second millennium BCE Hula Valley. (August 2020) - Marom, Nimrod; Bechar, Shlomit; Panitz-Cohen, Nava; Mullins, Robert A.; Yahalom-Mack, Naama
Highlights: Archeozoology is used to examine political economy in the MBA Hula Valley. The study region is suggested to have been dominated by a dimorphic political entity during the earlier part of the study period. Reversion to local, traditional Mediterranean animal economy indicates the dissolution of this entity in the middle of the second millennium BCE. Abstract: The Hula Valley, a gateway from Syria and Lebanon to the southern Levant, was dominated in the Middle and Late Bronze Ages by the city-state of Hazor. Following the desolation of the latter in the 13th century BCE, it seems that Abel Beth Maacah became the leading polity in the region, showing a remarkable sequence of Iron Age I architecture. We examine this regional power shift using a zooarchaeological sequence from Abel Beth Maacah, which suggests the economic impact of pastoral nomads on the region during the Middle Bronze Age, and a reversion to traditional, extensive agro-pastoralism in the Late Bronze and Iron Ages.